1993
DOI: 10.1038/eye.1993.36
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of flash electroretinograms recorded from Burian Allen, JET, C-glide, gold foil, DTL and skin electrodes

Abstract: Single flash scotopic and photopic electroretinograms (ERGs) were recorded from the same subjects using six types of corneal electrode, in order to assess their relative effectiveness. In addition, the ERG from a lower eyelid skin electrode was recorded to give an indication of the degree of attenuation to be expected from a skin electrode. On average, the scotopic ERG recorded from the Burian Allen electrode measured 471 microV (100%), and relative to this the b-waves recorded using other electrodes were as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
2
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 7 publications
3
35
2
2
Order By: Relevance
“…We found Vmax recorded using the DTL electrode to be around 2x larger for DTL than skin electrodes, for both PT PhNR and b-wave amplitudes, whilst Vmax for the BT PhNR amplitude was approximately 1.5x larger for DTL electrode responses. This is consistent with the magnitude of increased amplitude reported from signals recorded using DTL electrode compared with skin electrodes [44][45][46].…”
Section: Discussionsupporting
confidence: 88%
“…We found Vmax recorded using the DTL electrode to be around 2x larger for DTL than skin electrodes, for both PT PhNR and b-wave amplitudes, whilst Vmax for the BT PhNR amplitude was approximately 1.5x larger for DTL electrode responses. This is consistent with the magnitude of increased amplitude reported from signals recorded using DTL electrode compared with skin electrodes [44][45][46].…”
Section: Discussionsupporting
confidence: 88%
“…As reported previously, 27 we found larger peripheral responses due to stray light when no surround was added (Figure 2). Unlike Hood et al, 27 who used Burian-Allen electrodes, we used DTL electrodes, which gave poorer signal-tonoise ratio 43 but more comfort to our subjects. One of the major problems for our subjects was to overcome eye drift and maintain concentration and fixation especially in the rod protocol in which vision was indistinct.…”
Section: Discussionmentioning
confidence: 99%
“…Such factors include the resistive and capacitative characteristics of the materials from which the electrodes are made and coated with and the area of the recording surface. In addition, the amplitude recorded with skin electrodes is noisier, mainly as a result of electromyographic activity intervention (15) . However, it has been shown that even with reduced amplitudes, recordings with skin electrodes can be useful to differentiate between normal and abnormal responses, as long as an appropriate normative reference is used (16) .…”
Section: Discussionmentioning
confidence: 99%